Heuristic method for the modified model of capacitated arc routing problems - Muhamad Hafiz Masran (Institute of Engineering Mathematics, 2015)
The scopes of this study are as follows; the limitation for data collection is based on small town in Perlis residential area around Arau, Kangar and Kuala Perlis; the existing heuristics are used to solve the problem within the limit of MCARP models; the limitation of the vehicle capacity in range 5000 kilogram until 10000 kilogram based on the vehicle capacity used in Perlis state.